GSK-3 and Wnt Signaling in Neurogenesis and Bipolar Disorder - Valvezan, Alexander J.; Klein, Peter S. (Frontiers in Molecular Neuroscience, 2012)
The Wnt signaling pathway is critical for development of the mammalian central nervous system and regulates diverse processes throughout adulthood, including adult neurogenesis. Glycogen Synthase Kinase-3 (GSK-3) antagonizes the Wnt pathway and therefore also plays a central role in neural development and adult neurogenesis. As lithium, the first line of therapy for bipolar disorder (BPD), activates Wnt signaling by inhibiting GSK-3, much attention has focused on GSK-3 and Wnt signaling in the therapeutic response to lithium. However, GSK-3 also regulates other critical signaling pathways, including growth factor/neurotrophin signaling downstream of Akt. Here we will review the roles of GSK-3 in CNS development and adult neurogenesis, with a focus on the Wnt pathway. We will also discuss the validation of GSK-3 as the relevant target of lithium and the mechanisms downstream of GSK-3 that influence mammalian behavior.